Motorcycle Time: An Experiential Recreation in the Field of Industrial Engineering and Related Fields - Aguirre Alvarez, Yenny Alejandra (2024)
The Department of Industrial Engineering of the University of Antioquia has been developing a series of strategies to raise awareness of the importance of recreational exercises as a dynamic to actively strengthen the learning outcomes of students in the different courses of the Industrial Engineering and related programs. With a view to visibility, increase the impact on the academic community and improve learning through experiential experiences, we propose a game called Motorcycle Time in which concepts of ergonomics, methods and times, layout, inventory, production logistics, collaborative work and decision making will be put into practice. The methodology of this game is divided into three phases: the first one for conceptual appropriation, the second one is the development of the game according to the established instructions and the third one responds to the closing of the exercise from a previously designed workshop. It is expected that the development of this unprecedented game will allow students to strengthen the key disciplinary concepts in the profile of the Industrial Engineer and related through gamification exercises and meaningful learning.